Crickets - P.G. Koehler; R.M. Pereira; B.E. Bayer (EDIS)
This document provides an overview of crickets, their behavior, and management strategies. It details the types of crickets commonly found in buildings, their physical characteristics, and their potential to damage fabrics. The article emphasizes exclusion as the primary method of control, recommending sealing cracks and removing debris. It also discusses the use of insecticides and baits when necessary. The document highlights the importance of proper sanitation and lighting adjustments to prevent cricket infestations. Publication date: February 1993.